Increase in wild animal consumption across Central Africa - Mattia Bessone; Daniel J. Ingram; Katharine Abernethy; Sylvanus Abua; Sophie Allebone-Webb; Daniela Antonacci; Riyong Kim; Stephanie Brittain; Daniel Cornelis; Diane Detoeuf; Charles A. Emogor; Julia E. Fa; et al. (Nature, 2026)
Abstract While human activities are driving widespread declines in wildlife populations 1,2 , in Central Africa, the meat of wild animals, or wild meat, represents a major component of the diets of millions of people 3 . To halt faunal degradation while ensuring sustainable use of wildlife, it is crucial to understand the scale and drivers of wild meat consumption. Here, using data from over 12,000 households from 252 locations in Central Africa, we show that wild meat is a fundamental component of the diets of rural populations, accounting for 20% of the recommended daily protein intake, compared with 13% and 6% for those living in towns and cities. We estimate that the total annual biomass of wild meat consumed in Central Africa increased from 0.73 million to 1.10 million tonnes between 2000 and 2022, with increasing demand from towns and cities. To ensure that wild meat is available to rural communities, in accordance with the Sustainable Development Goals 4 and the Kunming–Montreal Global Biodiversity Framework 5 , reducing wild meat consumption in urban metropolises is key. While our results are based on the most comprehensive dataset available, the geographical coverage is incomplete and the dataset represents a minimal fraction of the entire population of Central Africa. Targeted studies are needed to validate our model and assess critical areas of intervention.